2017
DOI: 10.1021/acsami.7b05648
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Morphology of Nanoporous Copper Made from Intermetallic Phases

Abstract: Many application-relevant properties of nanoporous metals critically depend on their multiscale architecture. For example, the intrinsically high step-edge density of curved surfaces at the nanoscale provides highly reactive sites for catalysis, whereas the macroscale pore and grain morphology determines the macroscopic properties, such as mass transport, electrical conductivity, or mechanical properties. In this work, we systematically study the effects of alloy composition and dealloying conditions on the mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…9,10 In addition, the pH value, kind of electrolyte, and applied potential can be adjusted to the structure of spongelike materials by controlling the surface diffusion of the remaining noble metal in the presence of adsorbing ions or oxide-based passivation layers. 11,12 This enables the tailoring of the characteristic properties like ligament size, pore size, and chemical composition of the np materials over a broad length scale. 13−15 Although numerous research works have already been performed, there is still a need for understanding of the evolution of porous materials by dealloying.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 In addition, the pH value, kind of electrolyte, and applied potential can be adjusted to the structure of spongelike materials by controlling the surface diffusion of the remaining noble metal in the presence of adsorbing ions or oxide-based passivation layers. 11,12 This enables the tailoring of the characteristic properties like ligament size, pore size, and chemical composition of the np materials over a broad length scale. 13−15 Although numerous research works have already been performed, there is still a need for understanding of the evolution of porous materials by dealloying.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, during the dissolution of a less noble metal, the surface diffusion process of the remaining noble metal leads to the formation of nanosized ligaments and pores. Thus, the dealloying processes depend on the kinetics of the dissolution of the less noble metal and of the surface diffusion of the remaining noble metal as well as the mass transport processes at the interface between the electrolyte and the alloyed surface. , In addition, the pH value, kind of electrolyte, and applied potential can be adjusted to the structure of spongelike materials by controlling the surface diffusion of the remaining noble metal in the presence of adsorbing ions or oxide-based passivation layers. , This enables the tailoring of the characteristic properties like ligament size, pore size, and chemical composition of the np materials over a broad length scale. …”
Section: Introductionmentioning
confidence: 99%
“…18 Although CuNSs are unstable in acidic environments under anodic polarization or unbiased conditions, 19 their anodic treatment in alkaline solutions causes the formation of CuO x nanostructures exhibiting catalytic activity towards electrooxidation of various organic substances, such as L-tyrosine, 20 glucose, 21,22 hydrazine, 22 and water. 23,24 Even though there are a number of successful applications of noble metal (Pt and Pd) based nanocatalysts to electrochemical conversion of CO 2 , [25][26][27] copper is the most promising catalyst for the CO 2 RR yielding valuable, high energy density products such as hydrocarbons, [28][29][30][31] alcohols, 28,29,32 formic acid and other carbonyls. 28,29,[32][33][34][35] It was demonstrated that the morphology and therefore the electrocatalytic properties of Cu nanostructures towards the CO 2 RR can be tuned by the addition of phosphate and the electrodeposition potential 35 or appropriate selection of the Cu complex precursor.…”
Section: Introductionmentioning
confidence: 99%
“…For electrocatalysis the most useful are CuNSs deposited on conductive surfaces. This can be achieved by laser ablation of copper surfaces, 13,41 plasma etching, 19 dealloying, 30,31 electrochemical polishing, 53 thermal annealing, 54 or electrodeposition. 10,18,20,22,43,55,56 Gowthaman and John demonstrated that the applied substrate potential during Cu electrodeposition affects the geometry of the obtained deposit.…”
Section: Introductionmentioning
confidence: 99%
“…As Cu is rather electropositive, it is a natural candidate as an affordable material for dealloying processes based on corrosion in aqueous media. Nanoporous Cu has been prepared by dealloying from various alloys compositions that include -next to Cu -Mn [6,29,30], Al [31,32] and Zn [32,33], respectively. However, while Cu in clean air forms a thick oxide layer that passivates the surface [34], Cu and its oxides are readily dissolved in numerous electrolytes when oxygen is present [35].…”
Section: Introductionmentioning
confidence: 99%